The Reduction of Tertiary Phosphine Oxides by Silanes - Kovacs, Tamara; Keglevich, Gyorgy (Current Organic Chemistry, 2017)
The deoxygenation of tertiary phosphine oxides is an important reaction, as it provides useful intermediates and reagents, makes the available P-ligands useful in transition metal complexes, and regenerates wastes produced by the Wittig-, Mitsunobu and Appel reactions. Methods for the reduction of the P=O moiety comprising different metal and other hydrides, silanes and other species are surveyed, especially from the point of view of environmentally-friendly (green) chemistry, and practical applicability to be able to select the most suitable reagent. Oxalyl chloride converting the phosphine oxide to the corresponding chlorophosphonium salt may also be used, but this step should be followed by a reduction. Obviously, silanes are the reagents of choice. The most widespread, but corrosive trichlorosilane may be substituted by more userfriendly alternatives, such as phenylsilane, tetramethyldisiloxane (TMDS) and polymethylhydrosiloxane (PMHS). The latter two species are cheap, but of lower reactivity, however, they may be useful in microwave-assisted and solvent-free deoxygenations. Stereochemical and mechanistic aspects of the most often applied silane reductions are also discussed. In most cases, the P-configuration is preserved.
Keywords: phosphines